Acquisition of English Modal Verbs by Indonesian EFL Learners: A Corpus-Based Analysis of Learning Patterns - Aisyah Aulia Putri; Nurasia Natsir (International Journal of Educational Evaluation and Policy Analysis, 2025)
This corpus-based study explores the acquisition patterns of English modal verbs by Indonesian EFL (English as a Foreign Language) learners through a comprehensive analysis of learner language data. The study utilizes a specialized learner corpus consisting of 2.5 million words drawn from both written and spoken productions of 450 Indonesian learners, covering various proficiency levels. The research focuses on examining the frequency patterns, semantic distributions, and error types associated with modal verb usage across the learner corpus. The study employs a combination of quantitative corpus linguistic methods and qualitative error analysis to uncover developmental trends and persistent difficulties in acquiring English modals. The findings highlight a significant underuse of epistemic modality, which expresses degrees of certainty, and an overreliance on core modals like "can," "will," and "must." Additionally, learners systematically avoid more complex modal constructions that are semantically nuanced and less frequent in their linguistic output. The analysis also reveals notable cross-linguistic influences from Indonesian, particularly in the areas of politeness marking and the expression of certainty. These interference patterns suggest that Indonesian learners may transfer modal expressions from their native language, leading to specific errors in the usage of English modals. Based on the findings, the study proposes a usage-based pedagogical framework that integrates corpus-informed instruction with explicit semantic mapping of modal meanings. This framework encourages teachers to address modal verb acquisition by emphasizing frequency-based approaches, contrastive semantic analysis, and corpus-driven awareness-raising activities. The research suggests that by focusing on the form-meaning-function relationships of modals in authentic contexts, learners can better understand and produce English modals accurately and appropriately. The findings have significant implications for enhancing modal verb instruction in EFL classrooms, especially for Indonesian learners.